Knowledge And Payment Ability Relationship With Compliance With The Premium Of Jkn-Kis Mandiri Pringsewu - Yenny Marthalena Marthalena; Sunarmi Sunarmi; Debby Sanjaya (BIMA Journal (Business, Management, & Accounting Journal), 2021)
Based Health Profile of Indonesia, the coverage JKN of December 31, 2014 reached 53%, while the growing phenomenon today is the difficulty of access to health services for the poor, it is because of membership standalone increasing inconsistent with compliance in paying dues JKN. The purpose of this study was to determine the relationship of knowledge and ability to pay the premium payment compliance self JKN-KIS in district Pringsewu. The design used in this study is an analytic using cross sectional method. The population in this study were all participants who came to pay a premium self JKN-KIS in office BPJS district Pringsewu with a sample size of 90 people. The bivariate analysis in this study using chi square test. The survey results revealed between knowledge and ability to pay the premium payment compliance self JKN-KIS in district Pringsewu with p value = 0.001 and 0.043. It is necessary to review the regulations or policies that have been implemented, in the implementation process and in the formulation of plans related to the National Health Insurance program. The study must be sourced directly from the field whether it is the fee for fees, registration procedures, payment procedures, membership, quality of service or the willingness or ability to pay the community. The local government should record the poor citizens so that interventions can be made in data collection. So that it is hoped that the public will be exposed to information about health protection so that increasing awareness of the independent JKN-KIS premium payment can run well